Understanding “Evil”: A Closer Look at the Dark Tetrad’s Relations With HEXACO and Big Five - Nedeljković, Boban; Tucaković, Lana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
We aimed to explore to what extent the Dark Tetrad traits are represented by basic personality traits framed by HEXACO (Study 1; 150 participants, Mage = 32.15, SDage = 8.41) and the Big Five model (Study 2; 215 participants, Mage = 35.59, SDage = 13.65). Alongside correlation analysis, we employed a quasi-canonical analysis of covariance. The results showed that the core features of the Dark Tetrad are mapped on the negative poles of Agreeableness and Honesty-Humility from the HEXACO and Agreeableness from the Big Five. Despite the somewhat distinctive nature of Narcissism compared to other dark traits, the common features of the Dark Tetrad are partially represented in both models, but to a larger extent in HEXACO. In conclusion, we recommend using the HEXACO model as a proxy for assessing the core features of the Dark Tetrad in large-scale studies where measuring both basic and dark personality traits is not feasible.